Esensi Ajaran Etika Dalam Teks Geguritan Sang Tabe - Nengah Adi Widiastrawan; Gusti Ayu Puspa Yanti; I Made Gede Budhyastra (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
The study of the Geguritan Sang Tabe text in this paper has the desired objectives in accordance with the author's subjective. These objectives are described as follows; describe and understand a description of how the Relevance of the Teaching of Ethics in Geguritan Sang Tabe and understand the form of ethical teachings in Geguritan Sang Tabe as a reference on religious teachings that deserve to be implemented until now. The writing method used in this paper is the method of interpretation which is a method of interpretation that can be linked to various other literatures to seek discussion in accordance with the needs of this study. and the method of presentation is used interpretive-descriptive. The results of this study indicate that: The main obligation for humans is self-restraint, especially the lust (Tri Kaya Parisudha and Yama Bratha) that is contained in humans.